Supplemental enzyme in artificial diets for north african catfish larvae Clarias gariepinus Burchell, 1822 - Ucu Cahyadi; Dedi Jusadi; Ichsan Ahmad Fauzi; Ade Sunarma (Jurnal Iktiologi Indonesia, 2020)
Supplemental enzyme in artificial diets with difference doses for African catfish Clarias gariepinus (initial weight of 0.0048±0.0001 g and total length 0.7633±0.0392 cm) were examined for 12 days feeding trial. The aim of this study was to analyze the effectiveness supplemental enzymes in diets for growth performance of catfish larvae. Tubifex sp. (control) and a multi enzyme was included at the level of 0.00 (ME0), 1.00 (ME1) and 2.00 g kg-1 (ME2 diet as a test diets. Each of the four experimental diets was randomly assigned to four plicate groups. Larva was allocated into 150 L aquaria at a density of 1350 larvae per aquarium. Data was analyzed using SPSS 20, followed by Duncan’s test. The result showed that the survival rate and condition factors were no statistical difference between experimental diets and control group. The highest final length, final weight, total food consumption, villi length and enzymes activity were recorded in the Control (P<0.05) and significantly different with other treatments. Feed efficiency’s control significantly different with other. Harvest size distribution, in the small size group (1-2 cm) did not show significantly different, in the medium size group (2-3 cm) and large size group (3-5 cm) the Tubifex sp. treatment were significantly different from the other treatments (P<0.05) whereas between ME0, ME1 and ME2 treatments were not significantly different. Among the supplemental enzyme in test diets, ME2 can improve weight and total length 6.25% and 13.4%, respectively than ME0 treatment. The results suggested that enzyme supplementation can improve intestinal structure and growth performance of catfish larvae. The supplemental enzyme in diets with doses up to 2 g kg-1 can increase intestinal villi’s length but have not been able to increase fish growth performance as use worm. Abstrak Penambahan enzim pada pakan buatan dengan dosis berbeda untuk ikan lele Afrika Clarias gariepinus (bobot awal 0,0048 ± 0,0001 g dan panjang total 0,7633 ± 0,0392 cm) telah dilakukan selama 12 hari. Tujuan penelitian ini adalah untuk menganalisis efektivitas penambahan enzim pada pakan untuk pertumbuhan larva ikan lele. Cacing sutra (kontrol) dan multienzim ditambahkan pada pakan dengan dosis 0,00 g kg-1 (ME0), 1,00 g kg-1 (ME1) dan 2,00 g kg-1 (ME2) pakan. Masing-masing dari empat perlakuan disusun secara acak dengan empat ulangan. Larva ditebar dalam 150 L dengan kepadatan 1350 ekor per akuarium. Data dianalisis menggunakan SPSS 20, dilanjutkan dengan uji Duncan. Hasil menunjukkan bahwas intasan dan faktor kondisi tidak berbeda nyata antarperlakuan. Nilai panjang dan bobot akhir, jumlah konsumsi pakan, panjang vili dan aktivitas enzim tertinggi diperoleh pada kontrol (P<0,05) dan berbeda nyata dengan perlakuan yang lain. Efisiensi pakan kontrol berbeda nyata dengan perlakuan lainnya. Distribusi ukuran panen, pada kelompok kecil (1-2 cm) tidak menunjukkan perbedaan yang nyata, pada kelompok sedang (2-3 cm) dan kelompok besar (3-5 cm) kontrol menunjukkan perbedaan yang nyata, namun antara ME0, ME1 dan ME2 tidak berbeda nyata. Pada perlakuan pakan buatan yang ditambahkan enzim, ME2 dapat meningkatkan bobot dan panjang total 6,25% dan 13,4% dibandingkan ME0. Diduga bahwa penambahan enzim dapat meningkatkan struktur usus dan kinerja pertumbuhan pada larva lele Afrika. Penambahan enzim dengan dosis sampai 2 g kg-1 pakan dapat meningkatkan panjang villi usus, namun belum mampu meningkatkan pertumbuhan ikan sebagaimana penggunaan cacing.